Explanation: first find the slope m of the line passing through the
the 2 given points to calculate the slope m use the gradient formula ∙ x m = y 2 − y 1 x 2 − x 1 let ( x 1 , y 1 ) = ( 1 , 3 ) and ( x 2 , y 2 ) = ( − 5 , 6 ) m = 6 − 3 − 5 − 1 = 3 − 6 = − 1 2 given a line with slope m then the slope of a line
perpendicular to it is ∙ x m perpendicular = − 1 m hence m perpendicular = − 1 − 1 2 = 2 the equation of a line in slope-intercept form is. ∙ x y = m x + b where m is the slope and b the y-intercept here m = 2 y = 2 x + b ← is the partial equation to find b substitute ( − 2 , 7 ) into the partial equation 7 = − 4 + b ⇒ b = 7 + 4 = 11 y = 2 x + 11 ← is the required equation